2011
DOI: 10.1128/aem.02238-10
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia coli O157:H7 on Cattle Hides

Abstract: The objective of this study was to determine the time period that Escherichia coli O157:H7 survives on the hides of cattle. Extensive research has been conducted and is ongoing to identify and develop novel preharvest intervention strategies to reduce the presence of E. coli O157:H7 on live cattle and subsequent transfer to processed carcasses. If a reduction of E. coli O157:H7 levels in feces can be achieved through preharvest intervention, it is not known how long it would take for such reductions to be seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 34 publications
(50 reference statements)
1
18
0
Order By: Relevance
“…In this type of water body, for example, a stream, 5-10, or more samples are collected across the vertical depth and width [3]. Samples from surfaces such as hide, table, knife, and the likes can be obtained by sweeping a buffered peptone water with premoistened swabs or sponge on the sampling surface in a Z-pattern [4]. The sponge or swabs that covers approximately 400-1000 cm 2 are then put in 100 ml of tryptic soya broth for further processing.…”
Section: Introductionmentioning
confidence: 99%
“…In this type of water body, for example, a stream, 5-10, or more samples are collected across the vertical depth and width [3]. Samples from surfaces such as hide, table, knife, and the likes can be obtained by sweeping a buffered peptone water with premoistened swabs or sponge on the sampling surface in a Z-pattern [4]. The sponge or swabs that covers approximately 400-1000 cm 2 are then put in 100 ml of tryptic soya broth for further processing.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the implementation of government regulations and development of process interventions, food recalls and human illness related to E. coli O157 remain concerns around the world. Reducing the prevalence of this pathogen in cattle at the pre-harvest level has been highlighted recently as a critical control point to decrease the number of E. coli O157 entering the food chain [6], [7], [8], [9], [10]. Awareness of the risk factors that may increase the prevalence of E. coli O157 at the pre-harvest level can provide insights to develop intervention technologies to reduce its prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Cattle that excrete more than 10 4 colony forming unit (CFU)/g of cattle feces have been defined as super-shedders [9], [12]. The super-shedders are responsible for about 90% of the total number of bacteria in the cattle herd [9], [12] and raise the prevalence of cattle infected with this pathogen on farms, making them a high risk factor at the pre-harvest level [6], [7], [13]. However, colonization of this pathogen in cattle is usually asymptomatic due to the lack of Shiga toxin receptor, globotriaosylceramide (Gb3), in cattle endothelial cells [14] that prevents elimination of super-shedding cattle contaminated with this pathogen at farms.…”
Section: Introductionmentioning
confidence: 99%
“…Survival of E. coli outside the intestines depends on temperature, water activity, nutrition, pH, bacterial concentration, and competing microflora (Duffy et al, 2014). Arthur et al (2011) showed that STEC O157 on the hides of live cattle survived for up to nine days.…”
Section: Accepted Manuscriptmentioning
confidence: 99%